Модификация поверхности обжиговых материалов низкотемпературной плазмой; Известия вузов. Физика; Т. 58, № 9-2 - Власов В. А. Виктор Алексеевич; Волокитин Г. Г. Геннадий Георгиевич; Скрипникова Н. К. Нелли Карповна; Волокитин О. Г. Олег Геннадьевич; Шеховцов В. В. Валентин Валерьевич (2015, 2015)
Заглавие с экрана